Reading reference - Felder, Ekkehard; Jacob, Katharina; Schwinn, Horst; Busse, Beatrix; Große, Sybille; Gvozdanović, Jadranka; Lobin, Henning; Radtke, Edgar (Handbuch europäische Sprachkritik online, 2019)
The handbook is a periodical and multilingual online publication. The volumes published to date have already been downloaded more than 8,500 times. For readers who prefer the tactile pleasures of reading, a print version is available. Encyclopaedic articles are published successively on selected topics that highlight key issues in language criticism and that are of cultural relevance for the European perspective. The handbook is aimed at presenting a conceptual history of European language criticism. The handbook not only provides insight into the specific language cultures, but also compares and contrasts them.